Influence of Prenatal Environment on Androgen Steroid Metabolism In Monozygotic Twins With Birthweight Differences - Schulte, Sandra; Schreiner, Felix; Plamper, Michaela; Kasner, Charlotte; Gruenewald, Mathias; Bartmann, Peter; Fimmers, Rolf; Hartmann, Michaela F.; Wudy, Stefan A.; Stoffel-Wagner, Birgit; Wölfle, Joachim; Gohlke, Bettina (Journal of Clinical Endocrinology and Metabolism, 2020)
OBJECTIVE: Although low birthweight (bw) and unfavorable intrauterine conditions have been associated with metabolic sequelae in later life, little is known about their impact on steroid metabolism. We studied genetically identical twins with intra-twin bw-differences from birth to adolescence to analyze the long-term impact of bw on steroid metabolism. METHODS: 68 monozygotic twin pairs with a bw-difference of <1 standard deviation score (SDS; concordant; n = 41) and ≥1 SDS (discordant; n = 27) were recruited. At 14.9 years (mean age), morning urine samples were collected and analyzed with gas chromatography-mass-spectrometry. RESULTS: No significant differences were detected in the concordant group. In contrast, in the smaller twins of the discordant group, we found significantly higher concentrations not only of the dehydroepiandrosterone sulfate (DHEAS) metabolite 16α-OH-DHEA (P = 0.001, 656.11 vs 465.82 µg/g creatinine) but also of cumulative dehydroepiandrosterone and downstream metabolites (P = 0.001, 1650.22 vs 1131.92 µg/g creatinine). Relative adrenal (P = 0.002, 0.25 vs 0.18) and overall androgen production (P = 0.001, 0.79 vs 0.65) were significantly higher in the formerly smaller discordant twins. All twin pairs exhibited significant intra-twin correlations for all individual steroid metabolites, sums of metabolites, indicators of androgen production, and enzyme activities. Multiple regression analyses of the smaller twins showed that individual steroid concentrations of the larger co-twin were the strongest influencing factor among nearly all parameters analyzed. CONCLUSION: In monozygotic twin pairs with greater intra-twin bw-differences (≥1 SDS), we found that bw had a long-lasting impact on steroid metabolism, with significant differences regarding DHEAS metabolites and relative androgen production. However, most parameters showed significant intra-twin correlations, suggesting a consistent interrelationship between prenatal environment, genetic background, and steroid metabolism.
CRIS-Team Scopus Importer:2020-09-04
Keywords: androgens; androgen production; fetal programming; low birthweight; steroid hormones; twin-to-twin transfusion syndrome